The first assessment of grain yield and associated traits in durum wheat across a decade in Nepal - Thapa, Dhruba Bahadur; Subedi, Mahesh; Sapkota, Manoj; Bohara, Suman; Pokhrel, Keshab Raj; Aryal, Laxman; Acharya, Basistha; Tripathi, Santosh; Chaudhary, Chhotelal; Mahato, Bramanti; Timsina, Krishna; Govindan, Velu; et al. (Frontiers in Plant Science, 2024)
Rapid urbanization and evolving dietary preferences have heightened the demand for durum wheat and its derivatives in developing nations like Nepal. This study represents the first comprehensive exploration and evaluation of durum wheat genotypes in Nepal, addressing the escalating need for high-yielding varieties. The primary objective was to identify stable and prolific durum wheat lines for release, enhancing Nepal's durum wheat breeding program. Utilizing genotypes from CIMMYT's disease screening and yield nurseries from 2011/12 to 2020/21, a total of 132 genotypes, including international checks, underwent evaluation over ten years under the Alpha Lattice design. Results revealed significant variation among genotypes for grain yield and other traits, identifying highyielding and stable lines suitable for Nepal. Heritability analysis highlighted moderate heritability for grain number per spike, thousand-grain weight, and grain yield. Cluster analysis identified distinct clusters with high grain yield and desirable agronomic traits. Disease incidence facilitated the selection of resistant lines, with DWK38 emerging as the highest grain yielder (4416.04 kg/ha). Overall, durum wheat lines from CIMMYT exhibited robust performance in Nepal, enabling the identification of superior lines with potential benefits for farmers and consumers. The study's implications include developing and releasing superior durum lines in Nepal, providing farmers with profitable alternatives amidst evolving food habits. In conclusion, the findings from this study provide a valuable foundation for future durum wheat breeding efforts in Nepal, guiding the selection of genotypes that are wellsuited to the diverse environmental challenges of the region.